2.3 Functions
Ex: 1-23
- Function f:A→B - an assiagnment of exactly one element of B to each element of A.
- Domain and codomain, image and preimage, range
- One-to-one function
∀a∀b(f(a)=f(b)→a=b) or equivalently ∀a∀b(a≠b→f(a)≠f(b))
- Image of set f(s)={t∣∃s∈S,f(s)=t}
- Inverse function
1. If f is a function f:A→B and is one to one, then f−1 exists.
2. f−1(b)=a when f(a)=b
- Inverse image (hw 42, 44)
- Composite Function
Homework
p175: 40, 42, 44
40. Let f be a function from the set A to the set B. Let S and T be subsets of A. Show that
a. f(S∪T)=f(S)∪f(T).
Solution
we need to prove (1) f(S∪T)⊆f(S)∪f(T) and (2) f(S)∪f(T)⊆f(S∪T).
a1. Prove f(S∪T)⊆f(S)∪f(T)
Let b∈f(S∪T), it follows that ∃(a∈S∪T)f(a)=b
a∈S∪T⇒a∈S∨a∈T⇒(Or){a∈S⇒f(a)∈f(S)a∈T⇒f(a)∈f(T)⇒f(a)∈f(S)∪f(T)⇒b∈f(S)∪f(T)
Therefore a1 is proved.
a2. Prove f(S)∪f(T)⊆f(S∪T)
Let b∈f(S)∪f(T), it follows that b∈f(S)∨b∈f(T)
case 1: case 2: b∈f(S)⇒∃(a1∈S)f(a1)=ba1∈S⇒a1∈S∪T⇒f(a1)∈f(S∪T)⇒b∈f(S∪T)b∈f(T)⇒∃(a2∈T)f(a2)=ba2∈T⇒a2∈S∪T⇒f(a2)∈f(S∪T)⇒b∈f(S∪T)
In both cases, b∈f(S∪T). Therefore a2 is proved.
According to (a1) and (a2), a is true.
b. f(S∩T)⊆f(S)∩f(T).
Solution
Let b∈f(S∩T), it follows that ∃(a∈S∩T)f(a)=b
a∈S∩T⇒a∈S∧a∈T⇒(And){a∈S⇒f(a)∈f(S)a∈T⇒f(a)∈f(T)⇒f(a)∈f(S)∩f(T)⇒b∈f(S)∩f(T)
Therefore b is true.
Let f be a function from the set A to the set B. Let S be a subset of B. We define the inverse image of S to be the subset of A whose elements are precisely all pre-images of all elements of S. We denote the inverse image of S by f−1(S), so f−1(S)={a∈A∣f(a)∈S}. (Beware: The notation f−1 is used in two different ways. Do not confuse the notation introduced here with the notation f−1(y) for the value at y of the inverse of the invertible function f. Notice also that f−1(S), the inverse image of the set S, makes sense for all functions f, not just invertible functions.)
42. Let f be the function from R to R defined by f(x)=x2. Find
a. f−1({1})
Solution
f(x)=x2=1⇒x=±1f−1({1})={±1}
b. f−1({x∣0<x<1})
Solution
0<f(x)=x2<1⇒0<x<1 or −1<x<0f−1({x∣0<x<1})={a∈(0,1)∨a∈(−1,0)}
c. f−1({x∣x>4})
Solution
f(x)=x2>4⇒x<−2 or x>2f−1({x∣x>4})={a∈(2,∞)∨a∈(−∞,2)}
44. Let f be a function from A to B. Let S and T be subsets of B. Show that
a) f−1(S∪T)=f−1(S)∪f−1(T).
Solution
We need to prove (a1) f−1(S∪T)⊆f−1(S)∪f−1(T) and (a2) f−1(S)∪f−1(T)⊆f−1(S∪T).
a1. Prove f−1(S∪T)⊆f−1(S)∪f−1(T)
Let a∈f−1(S∪T), it follows that f(a)∈S∪T
(Or){f(a)∈S⇒a∈f−1(S)f(a)∈T⇒a∈f−1(T)⇒a∈f−1(T)∪f−1(S)
Therefore a1 is proved.
a2. Prove f−1(S)∪f−1(T)⊆f−1(S∪T)
Let a∈f−1(S)∪f−1(T), then a∈f−1(S)∨a∈f−1(T)
(Or){a∈f−1(S)⇒f(a)∈Sa∈f−1(T)⇒f(a)∈T⇒f(a)∈S∪T⇒a∈f−1(S∪T)
Therefore a2 is proved.
According to (a1) and (a2), a is true.
b) f−1(S∩T)=f−1(S)∩f−1(T).
Solution
We need to prove (b1) f−1(S∩T)⊆f−1(S)∩f−1(T) and (b2) f−1(S)∩f−1(T)⊆f−1(S∩T).
b1. Prove f−1(S∩T)⊆f−1(S)∩f−1(T)
Let a∈f−1(S∩T), it follows that f(a)∈S∩T
(And){f(a)∈S⇒a∈f−1(S)f(a)∈T⇒a∈f−1(T)⇒a∈f−1(S)∩f−1(T)
Therefore b1 is proved.
b2. Prove f−1(S)∩f−1(T)⊆f−1(S∩T)
Let a∈f−1(S)∩f−1(T), then a∈f−1(S)∧a∈f−1(T)
(And){a∈f−1(S)⇒f(a)∈Sa∈f−1(T)⇒f(a)∈T⇒f(a)∈S∩T⇒a∈f−1(S∩T)
Therefore b2 is proved.
According to (b1) and (b2), b is true.